Genome-wide transposon mutagenesis analysis of Burkholderia pseudomallei reveals essential genes for in vitro and in vivo survival - Wong, Yee-Chin; Naeem, Raeece; Abd El Ghany, Moataz; Hoh, Chee-Choong; Pain, Arnab; Nathan, Sheila (Frontiers in Cellular and Infection Microbiology, 2022)
Burkholderia pseudomallei, a soil-dwelling microbe that infects humans and animals is the cause of the fatal disease melioidosis. The molecular mechanisms that underlie B. pseudomallei’s versatility to survive within a broad range of environments are still not well defined. We used the genome-wide screening tool TraDIS (Transposon Directed Insertion-site Sequencing) to identify B. pseudomallei essential genes and approximately 500,000 transposon-insertion mutants of B. pseudomallei strain R15 were generated. Transposon-flanking regions were sequenced and gene essentiality was assessed based on the frequency of transposon insertions within each gene. A total of 848,811 unique transposon insertion sites were identified in the B. pseudomallei R15 genome and 492 genes carrying low insertion frequencies were predicted to be essential. Transposon mutants were grown in LB and M9 minimal medium to determine conditionally essential genes required for growth under laboratory conditions and 96 genes specifically required to support growth under nutrient-depleted conditions were identified. The Caenorhabditis elegans infection model was used to assess genes associated with in vivo B. pseudomallei survival. Transposon mutants were fed to the worms, recovered from worm intestines, and sequenced. Genes most likely involved in B. pseudomallei survival and adaptation in the C. elegans intestinal lumen, were identified. Two selected mutants were constructed and evaluated for the bacteria’s ability to survive and proliferate in the nematode intestinal lumen. When compared to wild type B. pseudomallei, a Tn5 mutant of bpsl2988 exhibited reduced survival in the worm intestine, was attenuated in C. elegans killing and showed decreased colonization in the organs of infected mice. The B. pseudomallei conditional essential proteins should provide further insights into the bacteria’s niche adaptation, pathogenesis, and virulence.